Фактори впливу на розвиток сільського зеленого туризму як малого підприємництва в Україні - Купріянчик, І.П.; Дорош, А.Й. (Економіка природокористування і сталий розвиток, 2019)
Розкрито фактори впливу на розвиток сільського зеленого туризму в громадах, а саме: наявність стратегії планування, туристичних ресурсів і транспортної доступності до них, відповідної інфраструктури, фахівців для ведення маркетингу та інтерпретації історичних і культурних надбань. Детальніше їх конкретизовано в наведеній структурній схемі та систематизовано за трьома напрямами: заохочувальні, стримувальні та потенційні. Доведено доцільність ідентифікації на законодавчому рівні надання послуг сільського зеленого туризму як малого підприємництва в громадах сіл, оскільки це найзручніший спосіб створення власного бізнесу без значних капіталовкладень. Наголошено на важливості коштів від сплати туристичного збору, які мають спрямовуватися виключно на розвиток сільського зеленого туризму на території громади, у тому числі здійснення обліку туристів, що дасть змогу оцінити туристичні потоки. It is established that the majority of economic entities in the agricultural sector (agroholdings) assign a significant share of land rent through the activities of corporate structures, which negatively affects the development of rural communities. There are no priorities for rural development and in the mid-term government's actions plan until 2020. Against this background, the need to introduce various forms of entrepreneurial activity (small and medium-sized businesses), among which rural green tourism occupies a prominent place, as Ukraine has significant tourism potential (natural, cultural, ethnic), has been proven. However, there is a nationwide problem for the provision of tourist services in rural communities due to the lack of planning strategies, adequate infrastructure, tourist resources and accessibility to them, the availability of people for marketing activities and the interpretation of historical and cultural assets. Some steps have been taken by the government to improve infrastructure development (subsidies from the state budget are allocated to local budgets and allocated between 806 united territorial communities in the amount of UAH 2.1 billion). The proposed article focuses on the factors influencing the development of rural green tourism as a micro-business that will help solve the socio-economic problems of the modern village. The above factors are systematized, presented in a structural and logical scheme and divided into: incentive, restraint, potential and specific. It is also established that the provision of rural green tourism services as a small business in rural communities is identified at the legislative level, as it is proved that this is the most convenient way to start a business without significant investment. The importance of the tourist tax payments, which have now increased by more than 20% and amount to 4.2 billion UAH, is emphasized as they should be directed exclusively to the development of rural green tourism. In this context, the records of tourists should be kept in order to evaluate the tourist flows in the community.